INNOVATIVE STRATEGIES OF THE HALAL INDUSTRY IN ADVANCING INDONESIA’S ECONOMIC GROWTH TRANSFORMATION - Miftah, Surur; Abdurahman; Naili Nuril Aufa Manik (JSE: Jurnal Sharia Economica, 2025)
Indonesia, as the country with the largest Muslim population in the world, possesses significant potential for developing the halal and sharia industries. However, this potential has not been fully optimized, particularly in the context of global competition. The halal nature of a product is a primary requirement for Muslim consumers, not only for food and pharmaceuticals but also for other consumer goods. The halal industry is now experiencing rapid growth, evolving beyond halal products to encompass a halal lifestyle. This research employs a normative legal approach with a library research method to delve deeper into the development of the halal industry in Indonesia. The findings reveal several noteworthy insights, including: 1) Increased Contribution to the National GDP. 2) Enhanced Global Competitiveness through Technological Innovation. 3) Economic Multiplication Effects and Support for MSMEs. 4) Sustainability and Green Industry in Halal Products.